Research Progress of Intramolecular π‐Stacked Small Molecules for Device Applications - Yang, Sheng‐Yi; Qu, Yang‐Kun; Liao, Liang‐Sheng; Jiang, Zuo‐Quan; Lee, Shuit‐Tong (Advanced materials (Weinheim), 2022)
Organic semiconductors can be designed and constructed in π‐stacked structures instead of the conventional π‐conjugated structures. Through‐space interaction (TSI) occurs in π‐stacked optoelectronic materials. Thus, unlike electronic coupling along the conjugated chain, the functional groups can stack closely to facilitate spatial electron communication. Using π‐stacked motifs, chemists and materials scientists can find new ways for constructing materials with aggregation‐induced emission (AIE), thermally activated delayed fluorescence (TADF), circularly polarized luminescence (CPL), and room‐temperature phosphorescence (RTP), as well as enhanced molecular conductance. Organic optoelectronic devices based on π‐stacked molecules have exhibited very promising performance, with some of them exceeding π‐conjugated analogues. Recently, reports on various organic π‐stacked structures have grown rapidly, prompting this review. Representative molecular scaffolds and newly developed π‐stacked systems could stimulate more attention on through‐space charge transfer the well‐known through‐bond charge transfer. Finally, the opportunities and challenges for utilizing and improving particular materials are discussed. The previous achievements and upcoming prospects may provide new insights into the theory, materials, and devices in the field of organic semiconductors. Unlike traditional covalent bond‐connected conjugated molecules, π‐stacked small molecules have special advantages in organic semiconductors. This review mainly focuses on the research development of π‐stacked molecular systems and introduces the new characteristics brought by the special molecular configuration and its application in organic semiconductors.